La Paca Digestora Silva, una herramienta para la Psicología Ambiental desde la perspectiva de la Teoría Ecológica (2021)
This research has as purpose to describe the change in the ecological behavior of Seventh Grade students (706) of the Instituto Técnico Santo Tomas de Aquino before and after the application of the psychopedagogical Paca Digestora Silva tool, which was achieved using some postulates proposed in environmental psychology, pedagogical tools and the creation of new materials, to transform pro-environmental behaviors; since it is proposed to provide a solution to the care of the environment with the training of new methodologies of care and prevention leading to transactional constructions. Moreover, it complies with the quasi-experimental research design, with randomization and the descriptive qualitative type, which allows to expand and clarify what was found with the creation and application of the instrument, which was used on two occasions during the research. Likewise, given the results, it is demonstrated that the students achieved to modify their behaviors in favor of environmental care.